Forest Farmer Group Development Model for Sustainable Well-Being in Kampar Regency - Gandhiko Mohta; Leti Sundawati; Budi Kuncahyo (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
Sustainable forest resource utilization can alleviate poverty in developing countries, including Indonesia, mainly by rural community groups like forest farmer groups (KTH). However, the capacity of KTH to manage forest resources is still low, leading to a decline in their well-being, exemplified in KTH in Kampar Regency. Unlike previous studies, this research focuses on developing KTH based on institutional, area management, and business aspects. The objective of the study is to analyze the factors influencing KTH’s well-being and build a development model for KTH. The research was conducted in Kampar Regency with 193 respondents using a census method. Data analysis used the Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique. The study’s findings reveal that business management significantly influences KTH’s well-being in Kampar Regency, followed by institutional and area management aspects. The development model for KTH involves enhancing key indicators in each aspect, such as KTH’s involvement in government/non-government organizations/other institution programs, appropriate area utilization, and increased business capital, as key steps to achieve a productive, self-reliant, prosperous, and sustainable management. Keywords: area, business development, forest farmer group, institutional, Poverty alleviation